The complete mitochondrial genome of the hybrid grouper Epinephelus lanceolatus (♀) × E. akaara (♂) - Kim, Jae Hoon (Mitochondrial DNA B Resour, 2018)
This study determined the complete mitochondrial genome of the hybrid grouper Epinephelus lanceolatus ♀ × E. akaara ♂. The complete mitochondrial genome is 16,743 bp long and includes 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes, and a control region. The nucleotide composition of the L-strand was as follows: A 20.00, C 14.10, G 29.21, and T 36.68%. All of the genes are encoded on the H-strand, except for NADH dehydrogenase subunit (ND6) and eight tRNA genes. A phylogenetic tree constructed using the maximum-likelihood (ML) method showed that the hybrid grouper E. lanceolatus ♀ × E. akaara ♂ is similar to E. lanceolatus.